Drosófilas e outros insetos associados a frutos de Parahancornia amapa dispersos sobre o solo da floresta - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1996)
Drosophila and other insects associated with fruits of Parahancomia amapa dispersed on the forest soil. One of the main challenges presented to those interested in studying evolutionary ecology has been to conceptualize, to define explain the patterns found in a community. The present study aims to investigate the relationships between species and resources in order to establish the degree to which this relationship can contribute to the patterns of abundance identified for the drosophilids in the Amazon region. It addresses 4 basic approaches 1. Study of the composition and structure of the community of all the insects associated to the fruit of Parahancomia amapa (Apocynaceae) dispersed on the ground, studied in three years of observation. 2. The composition, structure and distribution of abundance of the species members of the guild of drosophilids associated to the fruit. 3. The relationships between the drosophila and their resources, considering both fruit and yeasts associated with fruits and flies. 4. A preliminary assessment of the life cycle characteristics of the most abundant Drosophila species in this community. The basic methodology is the collection of fruits and laboratory monitoring of insect emergencies. Some field experiments are designed to answer specific questions about how species use resources. Laboratory experiments are used in life strategy studies (fecundity analysis, development time, and adult longevity). The results indicate high specific richness for this community, but the structure is marked by a low equitability among its components. Drosophila is the predominant group among insects. In the drosophila it was observed a gradual change of dominance, with ancestry of D.malerkotliana over the period, to the detriment of the dominant group, composed by the critical species of the subgroup willistoni, and of the other species that were becoming rarer, increasing the discrepancy between their abundances. D. malerkotliana is mainly associated to the fruits at the beginning of fermentation being predominantly attracted to the fruits at least one day before the other species, presenting priority effect. It has a high concentration of only one species of yeast, known as a strategist that is kloeckera apiculata, while the other species present greater diversification in the use of yeasts and use fruits in the phase of decomposition a little later. The distribution of all the drosophila was affected by fruit weight, tending to the highest concentration of flies in the heavier fruits and the total exclusion in fruits far below the average weight. The life strategies point to D. malerkotliana and the species of the subgroup willistoni as fast species, D. Sturtevanti shows to be a slow species. This species also stands out from the others as to the pattern of oviposition, development time and longevity. The growing success of D. malerkotliana observed in these three years of study has corresponded to the recent expansion of the species in the Amazon region and in the neotropical region as a whole. The first records of the species in the region date from the 70's and today the species is already among the group's dominant. Evaluation of this and other studies point to a combination of species characteristics (reproductive strategies and priority effect) and changes in habitat level, favoring its expansion and decline in guild diversity. These findings therefore indicate the possibility of using drosophilids as bioindicators of environmental changes occurring in relatively short periods of time.
Drosophila and other insects associated with fruits of Parahancornia amapa scattered on the forest soil
Keywords: Guilda; Fragmentos Florestais; Diversidade; Sitios de Criacao; Drosophila; Uso de Recursos; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA